UPAYA PENINGKATAN KINERJA MELALUI PENDIDIKAN DAN PELATIHAN DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI KALIMANTAN TENGAH: Efforts to Improve the Performance of Civil Servants through Education and Training at the Regional Office of the Ministry of Religious Affairs of Central Kalimantan Province - Nurhasanah (Pencerah Publik, 2023)
The performance of government organizations cannot be separated from the performance of civil servants as individuals in it. This condition shows that the competence of civil servants in Indonesia is a problem that needs serious attention. One of the efforts that can be taken in overcoming the problem of civil servant competence is through education and training (Diklat). Qualitative research with this phenomenological method will use performance management and effort theory. The approach used is phenomenology. Data collection techniques using semi-structured interviews, observations and documentation. The effort to send Administrator Leadership Training (PKA) which aims to develop participant competencies in order to meet managerial competency standards for administrator positions and propose supervisory leadership training (PKP) participants aims to develop participant competencies in order to meet supervisory managerial competency standards. In addition, it is also sought to send technical training participants to complement the technical capabilities of some employees in charge of certain technicalities and send administrative training participants to complement the administrative capabilities of several employees with a priority scale by considering budgets and other considerations. The inhibiting factors found in efforts to improve the performance of civil servants through education and training at the Regional Office of the Ministry of Religious Affairs of Central Kalimantan Province are the lack of available budgets to send training participants as needed, as well as the age factor and mastery of technology by the training participants sent so that the training results are not as expected.